Vitamin A fortification of Philippine, sweet flowing-type peanut butter - Pablo, Archie Owen Capote
The Philippine sweet, flowing type peanut butter was studied for fortification with vitamin A. The optimum temperature (130, 140 and 150°C and time (40, 50,60 minutes) of roasting peanuts after dry-blanching to produce a peanut butter that is most acceptable to consumers were determined using a 3x3 full factorial experiment in pilot scale. Vitamin A palmitate and β-carotene were used at different concentrations (100, 200, 300% of Philippine RDA for male adult) to determine the most-cost-effective fortificant to use that will meet Philippine regulations on vitamin A fortification of foods. Results of pilot scale experiments were applied and modified in industrial scale using he facilities of an industry collaborator. The point in process (with sugar before first grinding, with first-ground mixture before second grinding, during final mixing before dispensing product into jars) where the fortificant will be added that will give highest retention was likewise determined. Roasting 20 kg of dry-blanched peanuts at 140°C for 50 minutes gave a peanut butter that is most acceptable to consumers. Vitamin a palmitate was found cheaper (PhP1000.00/kg compared to PhP9200.00/kg beta-carotene). It is likewise a more bioavailabe form of vitamin A. A fortification level of 4.8 grams vitamin A palmitate for every 120kg peanut butter added during final mixing before dispensing product into jars was found to be sufficient to achieve the recommended level (1/3 of Philippine RDA per serving) in vitamin A-fortified foods in the Philippines